+0  
 
0
260
3
avatar

((e^x-e^(-x))/2)^2-1

math algebra
Guest Aug 23, 2014

Best Answer 

 #2
avatar+18827 
+10

((e^x-e^(-x))/2)^2-1

$$\left(
\dfrac{e^x-e^{-x}}{2}
\right) ^2
-1
=\sinh^2{x}-1 = \cosh^2{x}-2
=
\left(
\dfrac{e^x+e^{-x}}{2}
\right) ^2
-2
\\\\
( \cosh^2{x}-\sinh^2{x} =1 )$$

heureka  Aug 25, 2014
Sort: 

3+0 Answers

 #1
avatar+91409 
+5

 

 

$$\left( \frac{e^x-e^{-x}}{2}\right)^2-1\\\\
= \frac{(e^x-e^{-x})^2}{2^2}-1\\\\
= \frac{e^{2x}-2e^xe^{-x}+e^{-2x}}{4}-\frac{4}{4}\\\\
= \frac{e^{2x}-2+e^{-2x}}{4}-\frac{4}{4}\\\\
= \frac{e^{2x}+e^{-2x}-6}{4}\\\\
\mbox{Do you want me to keep going? It is probably finish now:)}\\\\
= \frac{e^{2x}+\frac{1}{e^{2x}}-6}{4}\\\\
= \frac{\frac{e^{4x}+1-6e^{2x}}{e^{2x}}}{4}\\\\
= \frac{e^{4x}+1-6e^{2x}}{4e^{2x}}\\\\
= \frac{e^{4x}-6e^{2x}+1}{4e^{2x}}\\\\$$

Melody  Aug 24, 2014
 #2
avatar+18827 
+10
Best Answer

((e^x-e^(-x))/2)^2-1

$$\left(
\dfrac{e^x-e^{-x}}{2}
\right) ^2
-1
=\sinh^2{x}-1 = \cosh^2{x}-2
=
\left(
\dfrac{e^x+e^{-x}}{2}
\right) ^2
-2
\\\\
( \cosh^2{x}-\sinh^2{x} =1 )$$

heureka  Aug 25, 2014
 #3
avatar+91409 
0

Thanks Heureka,

I had forgotten about cosh and sinh    

Melody  Aug 25, 2014

8 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details